Sustainability Model for Intelligent Community Centers of Costa Rica ] - Chen Mok, Susan (2015)
This article presents a working model to allow the sustainability of Intelligent Community Centers (CECI); its purpose is continuing with the processes for the local communities to own the technology, and therefore reduce the digital gap. Before presenting the model, we provide the conceptual background that provides the basis for CECI. In order to develop the model, in 2014 we conducted a diagnosis of the operation and administration of some CECI which exist in the Central County of Puntarenas, that are located within a maximum of 12 km from the Pacific Campus of the University of Costa Rica, and we studied the local actors that could get involved in the model. We considered that it is possible to replicate the model across all CECI existing in the entire country, but considering the specific needs of the local communities where these centers are located.